PHENOL OXIDATION USING NATURAL ZEOLITE SUPPORTED METAL ION CATALYST - Sri Wardhani; Danar Purwonugroho; Diah Mardiana (Universitas Gadjah Mada, 2008)
Phenol which contained in waste water has to be reduced and it could be done by oxygen oxidation. In order to increase the rate of reaction it was needed a catalyst. In this research the capability of various catalysts, namely zeolite-Zn(II), zeolite-Cu(II) and zeolite-Co(II)in oxidation of phenol has been investigated. The aim of this research was to study the type of metal ion catalyst towards the percentage of oxidated phenol. The oxidation process were carried out in an aqueous phenol of 100 ppm with oxygen flow rate of 200 mL/min. in the presence of catalysts with 0.2M of initial impregnation concentration. The capabilities of catalysts were performed by calculating the activation energy and it was done at two different temperatures, i.e. 70 and 90 oC. The percentage of oxidated phenol was determinated by measuring its concentration using UV-VIS spectrophotometer. In addition, the impregnated metal was calculated by measuring the ion concentration remains in the filtrate solution and it was determined using Atomic Absorption Spectrophotometer. The results showed that metal ion types affected the catalytic activity. The order of phenol oxidationactivity decreased as Co(II) > Cu(II) > Zn(II). The surface characteristics of catalysts were supported by pore volume and pore diameter i.e 0.009 cm3/g and 16.59 Å for Zn(II) whereas specific surface area was 10.32 m2/g for Zn(II), 0.004 cm3/g and 24.37 Å for Cu(II) whereas specific surface area was 3.57 m2/g for Cu(II), 0.001 cm3/g and 19.63 Å for Co(II) whereas specific surface area was 10.26m2/g for Co(II).